2018
DOI: 10.1111/ajad.12805
|View full text |Cite
|
Sign up to set email alerts
|

Expanding access to buprenorphine treatment in rural areas with the use of telemedicine

Abstract: Background and Objectives The opioid epidemic in the United States has resulted in a public health emergency. Medication‐assisted treatment (MAT) with methadone and buprenorphine are evidence‐based treatments for opioid use disorder. However, numerous barriers hinder access to treatment in rural areas. The use of telemedicine to deliver psychiatric services is demonstrated to be safe and effective; however, limited data exist on the novel application of telemedicine in the delivery of MAT. This report describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
88
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 25 publications
2
88
2
Order By: Relevance
“…75,76 Evidence shows that telemedicine can be an effective method to manage buprenorphine. 77 This is especially true now during the COVID-19 pandemic. Rhode Island, for example, has developed a hotline for those wishing to start buprenorphine.…”
Section: Explore Alternative Patient Care Methodsmentioning
confidence: 98%
“…75,76 Evidence shows that telemedicine can be an effective method to manage buprenorphine. 77 This is especially true now during the COVID-19 pandemic. Rhode Island, for example, has developed a hotline for those wishing to start buprenorphine.…”
Section: Explore Alternative Patient Care Methodsmentioning
confidence: 98%
“…This higher retention rate in patients undergoing treatment for opioid use disorder may be alluding to the social and logistical barriers patients may face while undergoing OAT that requires face-to-face interactions [ 13 , 14 ]. Furthermore, previous studies have demonstrated that telemedicine was non-inferior to in-person encounters for patients undergoing OAT, evidenced by no significant statistical differences in additional substance use or average time to abstinence [ 17 , 18 ]. Recent consensus guidelines by Shanthanna et al and Cohen et al both emphasize the use of telemedicine platforms to facilitate patient interactions for opioid therapy during social distancing restrictions in light of the COVID-19 pandemic [ 19 , 20 ].…”
Section: Is Telemedicine An Appropriate Alternative For Opioid Managementioning
confidence: 99%
“…Telemedicine in addiction studies in the USA has shown beneficial outcomes. Telemedicine has been used for buprenorphine treatment clinically and Weintraub et al (2018) conducted a retrospective chart review of service users and found that this was effective at keeping service users within treatment at 3 months of treatment with 86.1% having opiate negative tests suggesting very good outcomes. Zheng et al (2017) conducted a similar retrospective chart review, comparing outcome measures between telemedicine and face-to-face reviews for buprenorphine treatment.…”
Section: Telemedicine In Addictionsmentioning
confidence: 99%